Rancang Bangun Sistem Monitoring Suhu dan Kelembaban Udara Pada Ruang Server Berbasis Wireless Sensor Network - Wardhani Wardhani; Sirojul Hadi; Jian Budiarto (Jurnal Teknologi Terpadu, 2021)
A server has a pivotal role that needs certain attention when the server starts up. The server has data such as important documents stored on the server computer database. One of the factors that obstacle the server performance is a room that has a high temperature or humidity. In addition, the administrator is not able to check the state of the server room frequently. The purpose of this research is to design a temperature and humidity monitoring system in a server room based wireless sensor network. The method used is wireless sensor network. This method pursues the network administrators to monitor the conditions of the temperature and humidity in the server room. The research results show that the error generated by the sensor is relatively small. The average error generated by the temperature sensor is 0.12985% and the error generated by the air humidity sensor is 0.611538%. The collected temperature and humidity data can be displayed and stored on the web application and mobile view